β-lactam antibiotics induce metabolic perturbations linked to ROS generation leads to bacterial impairment - Ye, Dongyang; Sun, Jing; Jiang, Ran; Chang, Jiashen; Liu, Yiming; Wu, Xiangzheng; Li, Luqi; Luo, Yihan; Wang, Juan; Guo, Kangkang; Yang, Zengqi (Frontiers in Microbiology, 2024)
Understanding the impact of antibiotics on bacterial metabolism is crucial for elucidating their mechanisms of action and developing more effective therapeutic strategies. β-lactam antibiotics, distinguished by their distinctive β-lactam ring structure, are widely used as antimicrobial agents. This study investigates the global metabolic alterations induced by three β-lactam antibiotics-meropenem (a carbapenem), ampicillin (a penicillin), and ceftazidime (a cephalosporin)-in Escherichia coli. Our comprehensive metabolic profiling revealed significant perturbations in bacterial metabolism, particularly in pathways such as glutathione metabolism, pantothenate and CoA biosynthesis, pyrimidine metabolism, and purine metabolism. Antibiotic treatment markedly increased reactive oxygen species levels, with meropenem reaching nearly 200 ± 7%, ampicillin at 174 ± 11%, and ceftazidime at 152 ± 7%. Additionally, β-lactam antibiotics elevated 8-OHdG levels to 4.73 ± 0.56-fold for meropenem, 2.49 ± 0.19-fold for ampicillin, and 3.19 ± 0.34-fold for ceftazidime; 8-OHG levels increased to 5.57 ± 0.72-fold for meropenem, 3.08 ± 0.31-fold for ampicillin, and 4.45 ± 0.66-fold for ceftazidime, indicating that oxidative stress enhances oxidative damage to bacterial DNA and RNA. Notably, we observed a selective upregulation of specific amino acids associated with cellular repair mechanisms, indicating a metabolic adaptation to counteract oxidative damage. These findings illustrate that β-lactam antibiotics induce a complex metabolic perturbations associated with ROS production, potentially compromising critical cellular components. This study enhances our understanding of the intricate relationship between antibiotic action and bacterial metabolism, providing valuable insights for developing effective strategies against antibiotic-resistant pathogens.